2017
DOI: 10.1021/acs.energyfuels.6b03458
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Carbon Dioxide Capture at High Temperatures by Tetraethylenepentamine Acetic Acid and Polyethylene Glycol Mixtures with High Capacity and Low Viscosity

Abstract: Ionic liquids (ILs) are investigated in many studies to capture CO 2 in recent years.However, almost all of these studies carried out the absorption of CO 2 by ILs at relatively low temperatures (lower than 333.15K or even around the room temperature). Besides, the viscosity of ILs increases dramatically after absorbing CO 2 which could reduce the absorption efficiency significantly. Reversible and efficient absorption of CO 2 at high temperatures was investigated by IL of tetraethylenepentamine acetic acid ([… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…11−13 Moreover, PEGs are inexpensive and have lower viscosity than ILs. 14 Some studies indicate that CO 2 also exhibits high solubility in PEGs due to the quadrupole interaction of CO 2 with polar ether oxy-gens. 15−17 Hence, some researchers use PEGs as a cosolvent for ILs to decrease the viscosity of ILs after CO 2 absorption.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…11−13 Moreover, PEGs are inexpensive and have lower viscosity than ILs. 14 Some studies indicate that CO 2 also exhibits high solubility in PEGs due to the quadrupole interaction of CO 2 with polar ether oxy-gens. 15−17 Hence, some researchers use PEGs as a cosolvent for ILs to decrease the viscosity of ILs after CO 2 absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Hui and Yang 18 reported that ILs of diethylenetriamine hydrobromide ([DETAH]Br) dissolved in PEG200 have a CO 2 absorption capacity of 1.184 mol/mol [DETAH]Br and a regeneration efficiency of 86.67% after five consecutive cycles. Similarly, Yu et al 14 investigated the CO 2 absorption by ILs of tetraethylenepentamine acetic acid ([TEPA]Ac) and PEG200 mixtures, and results show that the absorption capacity can reach 1.24 mol/mol [TEPA]Ac at 353.15 K. Some researchers have also tried using PEGs only as the solvent for primary or secondary amines. Li and co-workers 7 studied the PEG200 solution of diglycolamine (DGA) or MEA for CO 2 absorption, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poly­(ethylene oxide) (PEO) has been used for CO 2 separations as a liquid absorbent since the 1960s and was first applied in membrane applications in the late 1980s. , Favorable quadrupolar interactions between the ether oxygens in the polymer backbone and dissolved CO 2 result in high solubility and permeability. Currently, PEO is used in two major industrial separations: (1) as the main component of Selexol, an industrial acid gas absorbent, and (2) the Polaris membrane, which is the first commercial membrane used for CO 2 separation. , In the 50 years of the Selexol process, research interest in PEO for CO 2 separation has not declined. PEO has been cross-linked to make free-standing membranes ,, and has been incorporated as a membrane additive , or the soft-segment of block copolymer membranes to increase solubility. , PEO has also been used as a nonaqueous cosolvent for amine and ionic liquid (IL) solutions to increase regeneration efficiency and reduce corrosion, energy consumption, and viscosity. …”
Section: Introductionmentioning
confidence: 99%